Chronic Obstructive Pulmonary Disease-Derived Circulating Cells Release IL-18 and IL-33 under Ultrafine Particulate Matter Exposure in a Caspase-1/8-Independent Manner - De Falco, Gianluigi; Colarusso, Chiara; Terlizzi, Michela; Popolo, Ada; Pecoraro, Michela; Commodo, Mario; Minutolo, Patrizia; Sirignano, Mariano; D’Anna, Andrea; Aquino, Rita P.; Pinto, Aldo; Molino, Antonio; et al. (Frontiers in Immunology, 2017)
Chronic obstructive pulmonary disease (COPD) is considered the fourth-leading causes of death worldwide; COPD is caused by inhalation of noxious indoor and outdoor particles, especially cigarette smoke that represents the first risk factor for this respiratory disorder. To mimic the effects of particulate matter on COPD, we isolated peripheral blood mononuclear cells (PBMCs) and treated them with combustion-generated ultrafine particles (UFPs) obtained from two different fuel mixtures, namely pure ethylene and a mixture of ethylene and dimethylfuran (the latter mimicking the combustion of biofuels). UFPs were separated in two fractions: 1. sub-10 nm particles, named Nano Organic Carbon (NOC) particles, and 2. primarily soot particles of 20-40 nm and their agglomerates (200 nm). We found that both NOC and Soot UFPs induced the release of IL-18 and IL-33 from unstable/exacerbated COPD-derived PBMCs. This effect was associated to higher levels of mitochondrial dysfunction and derived reactive oxygen species, which were higher in PBMCs from unstable COPD patients after combustion-generated UFP exposure. Moreover, lower mRNA expression of the repairing enzyme OGG1 was associated to the higher levels of 8-OH-dG compared to non-smoker and smokers. It was interesting that IL-18 and IL-33 release from PBMCs of unstable COPD patients was not NLRP3/caspase-1 or caspase-8-dependent, but rather correlated to caspase-4 release. This effect was not evident in stable COPD-derived PBMCs. Our data suggest that combustion-generated UFPs induce the release of caspase-4-dependent inflammasome from PBMCs of COPD patients compared to healthy subjects, shedding new light into the biology of this key complex in COPD.